Fibroblast Growth Factor Receptor 1 Variants and Craniofacial Variation in Amerindians and Related Populations - Gomez Valdes, Jorge (2013)
Objectives: The polymorphic site rs4647905 of the FGFR1 gene was previously associated with a decrease in cephalic index (CI). Here, we evaluate the relationships between genotypes and cephalometric measurements and indices in one Mexican Native and two mestizo Mexican populations using two haplotype-tag SNPs (rs4647905 and rs3213849) that represent >85% of the FGFR1 variability, plus three other SNPs (rs2293971, rs2304000, and rs930828) situated nearby. In addition, we genotyped five South American natives, two European, one African, and one Siberian populations to evaluate their intra and intercontinental population diversity. Methods: The five SNPs were tested and the craniofacial measurements and indices were collected using standardized procedures. Principal Component Analysis was used to verify individual/population comparisons. Associations were performed through the generalized linear model (GLM), coefficient of determination R2 and linear regression tests. Results: We found a tendency for a decrease in CI in individuals homozygous for allele rs4647905C, regardless of the population to which they belong, though the effect is more pronounced in mestizo. When the GLM analyses were performed using the absolute/linear cephalometric measurements, a statistically significant association was found between four SNPs and head length in the mestizo population. Conclusions: FGFR1 polymorphisms, especially rs4647905, can have an important role in the normal human skull variation, primarily due to their influence in head length, which would affect other cephalometric absolute/linear measures as well as indices like CI as a result of the pervasive nature of the morphological integration that characterizes the human skull.